Experimental study of convective heat transfer distribution of non-interacting wall and perpendicular air jet impingement cooling on flat surface - Chetan Kumar; Vashista Ademane; Vasudeva Madav (Case Studies in Thermal Engineering, 2024)
An experimental study evaluated heat transfer with perpendicular and wall-impinging air jets on stainless steel foil, for Reynolds numbers Re = 3000, 5000, 8000, and 10000, where the perpendicular jet targets the bottom and the wall jet the top, creating a unique, non-interacting effect. Distances to nozzle diameter ratios for wall jets (S/d = 4, 6, 8, 10) and perpendicular jets (Z/d = 2, 4, 6, 8) were varied. Significant heat transfer increases were noted, with the Nusselt number rising by up to 49.20 % for a Z/d = 6 and S/d = 8 combination at Re = 5000. Improvements ranged from 10.03 % to 49.20 %, peaking when the jets' high heat transfer regions overlapped. Optimal performance for Re = 3000 was at S/d = 10, aligning the wall jet's maximum with the perpendicular jet's stagnation area. For Re = 5000 to 10000, optimal S/d values were 8 and 4 for Z/d = 6, 8 and Z/d = 2, 4, respectively. The Nusselt number increase ranged from 29.21 % to 46.57 % at S/d = 10 for Re = 3000, the highest among all tested values. Wall jet heat transfer downstream increased by 90–105 % over perpendicular jets in corresponding regions. Increasing the wall to perpendicular jet distance improved heat transfer near the stagnation point, suggesting this cooling method for high-density electronics like CPUs and GPUs.